2012
DOI: 10.4314/sajas.v42i3.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary starch source on milk production and composition of lactating Holstein cows

Abstract: The objective of this study was to evaluate the effects of four sources of starch on milk production and composition, nutrient digestion and blood metabolites of lactating Holstein cows. Four multiparous Holstein cows (708 ± 70 kg of body weight; 83 ± 9 days in milk) were used in a 4 × 4 Latin square design with 21-d periods. The concentrate portion of the diet contained wheat, barley, maize or potato as the primary source of starch. Intake of dry matter (DM) ranged from 18.7 kg/d to 19 kg/d, and was similar a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
1
11
1
1
Order By: Relevance
“…The lower rate of starch degradation could have released more fat precursors. Mosavi et al (2012) also observed slower ruminal degradation for corn starch compared with wheat, barley or potato, as well as increased acetate and butyrate production along with higher milk fat (3.43% vs. 3.12, 3.09, and 3.13%, respectively). Contrary to these findings, Chanjula et al (2004) did not observe differences in milk production and compositional quality by adding corn (low degradability) or cassava (high degradability) at two inclusion levels (55 vs. 75%).…”
Section: Effect On Milk Yield and Fat Contentmentioning
confidence: 90%
See 3 more Smart Citations
“…The lower rate of starch degradation could have released more fat precursors. Mosavi et al (2012) also observed slower ruminal degradation for corn starch compared with wheat, barley or potato, as well as increased acetate and butyrate production along with higher milk fat (3.43% vs. 3.12, 3.09, and 3.13%, respectively). Contrary to these findings, Chanjula et al (2004) did not observe differences in milk production and compositional quality by adding corn (low degradability) or cassava (high degradability) at two inclusion levels (55 vs. 75%).…”
Section: Effect On Milk Yield and Fat Contentmentioning
confidence: 90%
“…This rate varies with grain type and processing and generally occurs in the following order: wheat (32% h) > oat > barley (29% h) > potato (5% h) > corn (2% h) and sorghum (Callison et al, 2001;Mosavi et al, 2012). Krause et al (2002) reported lower ruminal pH in lactating cows fed high moisture corn vs. dried corn.…”
Section: Starch and Ruminal Acidosismentioning
confidence: 99%
See 2 more Smart Citations
“…Glucogenic-based ingredients consist of cereal grains and their milling by-products, molasses, beet and citrus pulps, roots and tubers such as cassava and potatoes and their by-products, and dried reclaimed bakery products (McDonald et al, 2002;Mosavi et al, 2012;Steyn et al, 2017). Fat increases the energy density of the diet (Schroeder et al, 2004), and in particular enhances plasma cholesterol, the major precursor for steroidogenesis, including luteal P 4 synthesis in postpartum cows .…”
Section: Introductionmentioning
confidence: 99%